Development of the essay in literature - Melton, Alice Maude (My University, 1898)
Introduction: In beginning a study of the essay we should first know something of the nature of this division of literature. The essay is an endeavor to elucidate within certain limits, the most important facts and thoughts concerning a chosen subject, and present them clearly and attractively to the reader. It is an attempt to attain the truth by grouping and generalizing facts in relation to the subject in hand, but is not usually very extensive or exhaustive. At the present the essay has almost unlimited breadth, and may treat of any subject, and is the name given to literary compositions which have no other specific name. There are two general types of essays: First, the earlier and more original type called the personal essay, in which the writer reveals himself. Studied form and formal processes are avoided, and it is very much like conversation. Second, the didactic essay in which the interest centers in the subject matter, the writer not revealing himself. It is planned, the thought logically developed, and it is addressed to the understanding.
Citation: Melton, Alice Maude. Development of the essay in literature. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Literature; Essay; Writer; Theses; Manuscripts (documents)